School Improvement Specialist Coaches Plus (SISC+) As a Component of Teachers Pedagogical Landscapes in Malaysia: A Descriptive Study - Noel Jimbai Balang, Zamri Mahamod, Nor Aishah Buang (International Journal of Advanced Science and Technology, 2020)
The School Improvement Specialist Coaches Plus (SISC+)  in Malaysia has been in operation since 2012 and offers support to teachers, a member of the professional education team in all the Malaysian districts, through their coaches. SISC+’s responsibilities are focused, according to the District Transformation Plan 3.0 (DTP 3.0), on awareness and expertise in aspects of the curriculum, teaching methods and evaluation. This study thus aimed at defining the degree of SISC+ competencies in pedagogical elements. Data were collected via a collection of questionnaires distributed nationally to 118 ICs and analysed using version 23 of SPSS. Throughout the analysis, descriptive statistics were used, which included frequency, mean score, standard deviation and percentage. The results showed that the degree of SISC+ competence in knowledge of pedagogy is high, with a mean score of 4.63, sd=0.469. The research findings proved that SISC+ is experienced and competent in the pedagogical aspects of the subject being taught. The results of this study presented insight into SISC+’s capacity to mentor teachers in school as well as its practice of quality teaching and learning (T&L). Besides, the school and social environment played a key role in engaging with the teachers and identifying their challenges. It is also acknowledged that the programmed SISC+ needs to be adequately understood and accepted by schools and educational authorities in order for it to achieve its objectives of teacher support. Physical spaces and collaboration environments will enhance what the coaches are trying to accomplish. Originality and importance of this study are the first of its kind in Malaysia, as it examined the competencies and experiences of coaches who are heavily involved in teacher-programmed instructional coaching. The authority must, therefore, provide assistance and cooperation to assure that SISC+ continues to be effective in providing teachers with professional coaching.